Efforts of Guidance and Counseling Teachers to Increase Student Activity in Group Guidance in Class VII Students of MTs Sunan Pandanaran - Fany Rifqoh (Ma'soem University, 2023)
This research can provide a contribution to thinking about the scientific discourse of guidance and counseling as well as contribute to the development and continuation of guidance services, especially in helping class VII MTS students to increase student activity in the classroom. The subjects in this research were Guidance and Counseling Teachers and class VII students at MTs Sunan Pandanaran. Meanwhile, the object of this research is the guidance and counseling teacher's efforts to increase student activity in the classroom through group guidance for class VII students at MTs Sunan Pandanaran. The analysis used in this research is descriptive qualitative. The results of the research show that the Guidance and Counseling Teacher's efforts to increase student activity in the classroom through group guidance can increase the activity of class VII students at MTs Sunan Pandanaran, namely through the group formation stage, transition stage, implementation stage, and termination stage. This can be seen from the results of analysis of interview data and observations of students who took part in group guidance activities, namely that students became more active in participating in group guidance such as asking, answering and participating, but it appeared that student activity was most difficult in the aspect of self-confidence in expressing opinions.